1996
DOI: 10.1016/s0741-5214(96)70271-9
|View full text |Cite
|
Sign up to set email alerts
|

Results of bypass to the popliteal and tibial arteries with alternative sources of autogenous vein

Abstract: AAV bypasses can provide overall results comparable with SSGSV bypasses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
1
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(54 citation statements)
references
References 12 publications
4
47
1
2
Order By: Relevance
“…17 Arm vein grafts had lower patency rates when compared with saphenous vein grafts. This is consistent with previous reports, 29 including the experience reported from our institution. 30 The reasons for this difference are multiple and probably not related to any flaw in the intrinsic biology of arm veins.…”
Section: Commentsupporting
confidence: 94%
“…17 Arm vein grafts had lower patency rates when compared with saphenous vein grafts. This is consistent with previous reports, 29 including the experience reported from our institution. 30 The reasons for this difference are multiple and probably not related to any flaw in the intrinsic biology of arm veins.…”
Section: Commentsupporting
confidence: 94%
“…Nevertheless, autologous saphenous vein is still the treatment of choice due to its long-term patency and resistance to infections [1][2][3][4][5]. Furthermore, Recommendation 40 of the TASC II states that the great saphenous vein (GSV) is a better conduit in which to perform femoro-distal bypass.…”
Section: Introductionmentioning
confidence: 99%
“…With the LSV, Calligaro et al 22 in 1997 and Weaver et al 23 in 1987 reported secondary patency rates of 34% at 2 years and 60% at 3 years, respectively. In a series of 133 bypasses with UEV and LSV, Gentile et al 24 reported a 5-year assisted primary patency rate of 72%. Despite these astounding results, UEV and LSV are rarely used for below-knee revascularization because of either long and tedious harvesting or poor quality.…”
Section: Discussionmentioning
confidence: 99%